Asset specificity and firm value: Evidence from mergers - Kim, Joon Ho (Journal of Corporate Finance, 2018)
This study explores the effect of asset specificity on a target firm's value in a merger. Using US merger data, I show that, when their industry experiences a negative cash flow shock, target firms that consist of more industry-specific real assets receive a lower merger premium than do those consisting of more generic assets. Results also suggest that the asset specificity discount in the target return is more pronounced if target firms are financially distressed. However, the negative value effect of asset specificity is mitigated in the presence of financially unconstrained industry rivals who place high value on the targets' assets, compete for the targets, and, thereby, are more likely to acquire the targets. Overall, the results are consistent with the hypothesis that asset specificity of a firm is an important determinant of the firm's value.